2023
DOI: 10.3390/pediatric15030038
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Clinical COVID-19 Mouthwashing Protocol and Potential Modulation of Pediatric Oral Bacterial Prevalence of Selenomonas noxia: A Pilot Study

Praneeti Sodhi,
Yuxin Jiang,
Summer Lin
et al.

Abstract: Dental office protocols to combat the SARS-CoV-2 (COVID-19) pandemic include mouth washing for an extended 60 s, thereby reducing detectable oral virus. However, it is unclear whether this protocol has any effects on the newly identified periodontal pathogen and obesity-related bacterium often found among pediatric patients, Selenomonas noxia. To determine if the mouthwash protocol has any measurable effect on S. noxia amongst pediatric patients, clinical pediatric saliva samples were obtained from pediatric p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 53 publications
2
7
0
Order By: Relevance
“…Many other studies have found significant differences between males and females with respect to the development and progression of periodontal disease and the prevalence of specific periodontal pathogens [ 36 , 37 , 38 ]. The lack of sex-specific associations with this organism is consistent with other recent studies that have included both pediatric and adult patient populations, strongly suggesting that the traditional risk factors of sex and age may not be the most important factors to determine which patients harbor Selenomonas [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Many other studies have found significant differences between males and females with respect to the development and progression of periodontal disease and the prevalence of specific periodontal pathogens [ 36 , 37 , 38 ]. The lack of sex-specific associations with this organism is consistent with other recent studies that have included both pediatric and adult patient populations, strongly suggesting that the traditional risk factors of sex and age may not be the most important factors to determine which patients harbor Selenomonas [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 86%
“…The samples were then processed to isolate DNA, as previously described [ 24 , 25 , 26 ]. In brief, the TRizol reagent from Fisher Scientific (Fair Lawn, NJ, USA) was used to perform DNA extractions from each sample according to the manufacturer’s recommendations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent studies from this group have revealed that some pediatric patients, with and without orthodontic brackets, also harbor this organism [14,15]. This may be of particular concern as this gram-negative anaerobe typically found in periodontitis may also colonize the gastrointestinal tract and has been strongly associated with overweight and obese adults [16,17].…”
Section: Introductionmentioning
confidence: 99%